Quality of care in Telehealth service in the context of pandemic, bibliographic review - Roberto Pelayo Mosqueira Moreno; Araceli del Milagro Gonzáléz Castillo; Flor Delicia Heredia Llatas (Acta Médica del Centro)
Introduction: Telehealth in times of pandemic became an alternative for patient care due to social confinement measures and was used both in primary care and in the different medical specialties, with satisfaction levels similar to face-to-face consultation. Objectives: to evaluate the quality of telehealth care in the context of a pandemic and to determine the benefits and barriers that hinder this type of care. Methods: through a systematic process, we accessed documents from different databases such as Scopus, ScienceDirect, SciELO, Google academic and Proquest in the period between 2018 and 2022, in English and Spanish, open access and descriptive type research; the descriptors quality of care, quality, telehealth and satisfaction were used. Their quality was assessed, their results were analyzed and their contributions were critically systematized. Conclusions: there are no differences between the quality of telehealth care and traditional care, its main benefits lie in access to care and cost reduction, and its barriers are the problems of technological gaps and the lack of training of health personnel in its use.